Thermal and phase change process analysis in a porous vented circular cavity under the impacts of inner rotating surface and inclined magnetic field during nanoliquid convection - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2023)
In this study, thermal and phase change process in a circular porous vented cavity (P-VC) are numerically analyzed with finite element method considering magnetic field and inner surface rotation during nanofluid convection. The control of convective heat transfer and thermal management in porous cavities are crucial in applications for electronic cooling, heat exchangers, convective drying, and many other heat transfer devices. The numerical analysis is carried out for various values of the relevant parameters (Reynolds number-Re, rotational Reynolds number-Rew, Hartmann number-Ha, opening ratio-Ri) as follows: 500 & LE; Re & LE; 2000, -5000 & LE; Rew & LE; 5000, 0 & LE; Ha & LE; 80, 1 & LE; Ri & LE; 3. The phase change process often accelerates with higher Re when rotations are active. The rotations cause the full phase transition time (TR) to decrease by roughly 15% at the highest Re. The phase change process speeds up when both CW and CCW rotations are used at their highest values. The impacts of Ha on the TR variation is found as 33%. The thermal performances are slightly influenced by the variation of inner surface rotations and magnetic field strength. However, highest impact on thermal process and phase change is obtained when varying the inlet port size. The TR variation becomes 57% while heat transfer enhancement factor is obtained as 3.5. The optimal parameter combination to provide the highest thermal performance is (Ha, Rew, Ri) = (30.85, -4145, 2.98).
Keywords: Phase change; Magnetic field; Cylindrical vented cavity; FEM; Rotation